ANALYSIS OF MARKETING STRATEGY THROUGH MULTIMEDIA IN INCREASING THE SALES OMZET OF ASUS BRAND PRODUCTS AT TOWER COMPUTER PONTIANAK SHOP - Widansyah, Gani; Sumartono, Bambang Genjik; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the marketing and multimedia strategiesused to increase sales turnover of Asus brand products at the MenaraComputer Pontianak store. The research method used is descriptivewith a case study research form. The data sources for this study were10 shop owners, shop employees and customers of the MenaraComputer Pontianak store who had bought Asus brand products. Theresults of the study show that the marketing strategy used is 9P,namely product, price, promotions, place, process, people, physicalevidence, payment and packaging. Various kinds of multimedia thathave been used, namely print media such as magazines andbrochures, electronic media such as television, outdoor media such asbillboards, banners, posters and neon boxes, bottom line media suchas exhibitions and digital media such as websites, sms, marketplace,shopee and tokopedia as well as social media whatsapp, instagram,youtube and facebook. Based on the results of the study, the salesturnover of Asus brand products in 2019 and 2022 has increased anddecreased or fluctuated every month.